RANCANGAN ADMINISTRASI DAN INFORMASI PADA PT. BRAHMA BINABAKTI - Susanto, Darex (FORTECH (Journal of Information Technology), 2019)
Utilization of information technology becomes a requirement that is used to improve or assist company performance. Every company seeks to build a system that can help and simplify its performance. Administrationis the whole process of cooperation between two or more people based on a certain rational in order to achieve goals that have been predetermined. This thesis describes the stages in building an administrative information system at PT. Brahma Binabakti who can help and facilitate in the operations performed. So as to provide information more quickly, accurately and relevant, minimize errors and facilitate the search data when necessary, save time in data processing, reporting can be done easily and quickly using crystal reports. This information system is built using visual basic programming language net 2010 and MySql database.